Rhizospheric actinomycetes from organic crops of native potato (Solanum tuberosum): isolation, phenotypic characterization, molecular identification, and impact on biocontrol of Phytophthora infestans (Mont.) de Bary - Chumpitaz Bermejo, Astrid (2020)
Potato (Solanum tuberosum L.) is the fourth most consumed food crop in the world, whose production in Peru is diminished due to phytosanitary problems and high costs of chemical fertilizers. In the present work, 32 actinomycetes isolated from the rhizosphere of organic native potato crops collected in the town of Cabana, Lucanas, Ayacucho, were characterized phenotypically and evaluated for their in vitro antagonistic capacity against Oomycete phytopathogen Phytophthora infestans. The characterization tests showed that 97% of the actinomycetes were able to assimilate glucose, sucrose, and mannitol; as well as producing extracellular enzymes like amylases (100%) and cellulases (50%). Furthermore, the growth in laboratory culture was better in the range of pH 5.5-8.5 and temperature 28-30 °C. From the tests of antagonism in oat agar (71.9%) and rye agar (31.2%), three strains were selected according to the native potato variety were selected as CAB10-J2 (Ccompis), CAB9-CA4 (Cuchipa-akan) and CAB5-F5 (Futis) with pathogen inhibition rates of 80.05, 77.47 and 37.5% respectively. The strains were identified by molecular tests as members of the genus Streptomyces and owners of polyketide synthase (PKS) genes. It is concluded that the rhizospheric actinomycetes of potato are producers of bioactive compounds capable of remarkably inhibiting the pathogen Phytophthora infestans, being able to be considered candidates in biological control programs of the "potato blight".